Undernourishment and tuberculosis: two flagella of underdevelopment. A case assisted in Timor Leste - Anagalys Ortega Alvelay; Marcos Félix Osorio Pagola; Pedro Juan Barrios Fuentes; Sol Esther García Morales (Medisur)
Undernourishment continues to be a serious health problem in several regions worldwide and poverty its main and determinative underlying cause. In children, it establishes a favorable field for the development of infectious diseases among them malaria, acquired immunodeficiency syndrome and tuberculosis which simultaneously favour the maintenance of undernourishment and health lethality. In this report, the case of a 5 year- old undernourished girl, who was assisted by the cuban medical staff in Temor Leste, is presented. The patient is diagnosed as a case of pulmonary tuberculosis after a previously prolonged disease associated to malaria, acute respiratory diseases and intestinal parasites which motivated a stepped clinical assistance and further hospital admissions. The patient is still under medical treatment.